PTH-173 Introduction of the Team Brief and who Safety Checklist in Endoscopy. (4th June 2013) - Vinnamala, S; Disney, B; Mohammed, I; Chapman, W; Fogden, E
Abstract : Introduction: The World Health Organization (WHO) launched the Global Patient Safety Challenge, 'Safe Surgery Saves Lives' 1, in 2008 with the aim of reducing the number of deaths and adverse events resulting from surgical procedures. Central to this initiative is the WHO checklist that covers the various phases of a procedure. This checklist was modified and used for all endoscopic procedures performed in our trust. The Aim: of the survey was to gather opinions from endoscopy staff about the recently introduced team debrief and the modified WHO checklist for endoscopy in our trust. We aimed to assess the staff's perception of the impact of the checklists (positive or negative) on patient safety, communication and team behaviour, staff satisfaction and their general effectiveness. We also aimed to assess the need for training on the use of the checklists and their potential to drive improvement with an additional section for their comments. Responses were obtained from the different grades of staff including nurses, health care assistants, trainees and consultants. Methods: We designed a questionnaire according to the LIKERT2 scale, where the respondent could choose between five options including one neutral stance and the other four with varying degrees of agreement or disagreement with sixteen questions covering the above mentioned key categories. Participation in the survey was anonymous and voluntary. Results: 78 staff across two hospitals of the trust responded to the survey, of which two were incomplete and hence excluded from analysis. Respondents included consultants (20), Specialist Registrars (8), nurses (29), health care assistants (12) and unknown (7). 81% perceived an improvement in patient safety and 75% in team communication. 75% were satisfied with the checklists. 80% believed that the checklists have the potential to drive improvement with 96% of them wanting to continue using these. The only negative aspect from the survey was that almost a half of the respondents (48%) felt that their feedback was not acted upon. 100% agreed that all staff needed to participate actively in the checklist and team briefs. Conclusion: Our results suggest that the introduction of the adapted WHO checklist has been a positive experience based on this staff survey, enhancing patient safety and staff communication. This adapted checklist will continue to evolve based on staff feedback. We suggest that all endoscopy units should introduce an adapted WHO checklist and we understand that the BSG is developing one currently. Disclosure of Interest: None Declared. References: Safe Surgery Save Lives - WHO/IER/PSP/2008.07 Public Opinion and the Individual. Gardner Murphy and Rensis Likert. New York: Harper & Brothers, 1938